Communication Planning In The Development Of Students' Morals At SD Fatma Kenanga Foundation In Bengkulu - Eggy Pramana Putra; Sapta Sari; Yanto Yanto (Penerbit Jurnal Indonesia, 2022)
This study aims to determine Communication Planning in the moral development of students at SD Fatma Kenanga Foundation Bengkulu. This study uses a qualitative method using descriptive analysis. In this study, Scoot M. Cutlip & Center's communication planning theory is used as an analytical tool. The results of the study that communication planning plays an important role in fostering student’s morals at Fatma Kenanga Foundation Bengkulu as follows: Fact Finding, regarding the findings of student’s problems related to moral development. The problem is that there are still students who are still rude, speak impolite, and are indifferent to their teachers. Planning, the planning program implemented by SD Fatma Kenanga Bengkulu is communication planning using 5 language continuums and the application of children's character pillars. tolerant and peace-loving. Communication Action, in terms of communication action, teachers apply a 5-continuum language learning system in classroom learning. This 5 language continuum is very effectively applied to students at SD Fatma Kenanga Bengkulu. Evaluation, communication planning programs are always evaluated by holding regular meetings with the principals and teachers. For student evaluation, namely with report cards, questionnaires or questionnaires distributed to parents and peers.